2005
DOI: 10.1615/jenvpathtoxoncol.v24.i3.70
|View full text |Cite
|
Sign up to set email alerts
|

Black Tea Extract Can Modulate Protein Expression of H-ras, c-Myc, p53, and Bcl-2 Genes During Pulmonary Hyperplasia, Dysplasia, and Carcinoma In Situ

Abstract: Lung cancer has emerged as one of the leading causes of cancer death in most developed and many developing countries of the world. In the absence of effective screening and early detection methods of lung cancer and overall poor prognosis, the 5-year survival following treatment has not improved significantly over the last two decades. It is hoped that the risk of the disease can be minimized by preventive measures. One aspect of lung cancer prevention emphasizes the cessation of tobacco smoking, and another s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
6
1
1
Order By: Relevance
“…Our study in vitro using a human lung cancer cell line NCI-H460 has shown reduction of cell proliferation and induction of apoptosis [37]. Analysis of p53, bcl-2, c-myc and H-ras expression revealed up regulation of p53, down regulation of bcl-2 and no significant change on H-ras and c-myc expression by the tea compounds, which is different from the observation of our in vivo study [38] where down regulation of H-ras and c-myc was noted.…”
Section: Introductioncontrasting
confidence: 88%
“…Our study in vitro using a human lung cancer cell line NCI-H460 has shown reduction of cell proliferation and induction of apoptosis [37]. Analysis of p53, bcl-2, c-myc and H-ras expression revealed up regulation of p53, down regulation of bcl-2 and no significant change on H-ras and c-myc expression by the tea compounds, which is different from the observation of our in vivo study [38] where down regulation of H-ras and c-myc was noted.…”
Section: Introductioncontrasting
confidence: 88%
“…Another explanation is that normal cells are resistant to the tumor necrosis factor related apoptosis-inducing ligand (TRAIL) due to the high TRID levels, whereas tumor lines carrying TRAIL-receptors in most cases can not be protected ( 31 ). Theaflavins have been reported to target the Fas/caspase-8 pathway to induce apoptosis in human breast cancer cells, and influence Bcl-2 protein expression in an experimental lung cancer mouse model ( 32 , 33 ). In this study, treatment with TF3 significantly regulated the protein expression of Bcl-2 family proteins (Bax, Bad and Bcl-xL), DR5, FADD, caspase-8 and -9 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the decreased p53 nuclear factor-dependent transcriptional activation induced by dactylone was verified using nonparametric statistical method MannWhitney U test (computer program Statistica 6.0, StatSoft). The tumor-suppressor p53 protein plays a critical role in apoptosis and an increase of p53 protein production followed by apoptosis is a common characteristic effect of cancer-preventive agents such as resveratrol (25), black tea extract (26), and many others. However, in our case, we did not observe an increase in p53 protein levels, although apoptosis was induced by dactylone.…”
Section: Cancer Researchmentioning
confidence: 99%